Upaya Peningkatan Prestasi Belajar Bahasa Indonesia melalui Model Pembelajaran Role Playing - Agustina Eka Apsara (utile: Jurnal Kependidikan, 2021)
This Classroom Action Research aims to improve process skills in applying concepts and acting as well as improving student learning outcomes of SMPN 12 Sukabumi City in Indonesian subjects in order to obtain a predetermined minimum score of 76 and 80% achieve the KKM score. This Classroom Action Research uses the Role Playing model. The type of research used is classroom action research (CAR) using Kemmis and Taggart designs. Through 2 cycles starting from planning, implementation, and reflection. The participants in this study were 34 students of class VIII H consisting of 18 female students and 16 male students. Data collection tools using tests and observation sheets. The results of data processing from observations of each meeting in cycles I and II as well as student learning outcomes obtained through tests at the end of cycles I and II showed that there was a significant increase in student activity.